Effectiveness and Safety of Tofacitinib in the Management of Ulcerative Colitis: A Brazilian Observational Multicentric Study - Parra, Rogerio S. (2024)
Univ Sao Paulo, Ribeirao Preto Med Sch, Sao Paulo, Brazil